2004
DOI: 10.1111/j.0022-1112.2004.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

A dual enzyme method for the establishment of long‐ and medium‐term primary cultures of epithelial and fibroblastic cells from Atlantic salmon gills

Abstract: A dual enzyme disaggregation method using collagenase and then trypsin was developed that allowed the reproducible initiation of primary cultures from Atlantic salmon Salmo salar gills. Cultures had both epithelial and fibroblast morphology and persisted for an average of 20 passages. Growth was dependent upon a minimum concentration of 5% foetal calf serum (FCS) for fibroblasts and 10% FCS for epithelial cells. Growth was mostly independent of substrate, although epithelial cells showed increased growth on ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Primary cultures of gill epithelial cells from juvenile Atlantic salmon (5-10 g) were isolated as previously described [48], with some modifications. Briefly, fish were euthanized by anaesthetic overdose in ethyl 3-aminobenzoate methanesulfonate salt (Sigma-Aldrich), gill arches excised, washed in phosphate buffer saline (PBS) without Ca 2 + and Mg 2 + containing 200 μg/mL Penicillin/Streptomycin (Invitrogen), 400 μg/mL gentamicin sulfate (Lonza), and 2.5 μg/mL Amphotericin B (Lonza).…”
Section: Methodsmentioning
confidence: 99%
“…Primary cultures of gill epithelial cells from juvenile Atlantic salmon (5-10 g) were isolated as previously described [48], with some modifications. Briefly, fish were euthanized by anaesthetic overdose in ethyl 3-aminobenzoate methanesulfonate salt (Sigma-Aldrich), gill arches excised, washed in phosphate buffer saline (PBS) without Ca 2 + and Mg 2 + containing 200 μg/mL Penicillin/Streptomycin (Invitrogen), 400 μg/mL gentamicin sulfate (Lonza), and 2.5 μg/mL Amphotericin B (Lonza).…”
Section: Methodsmentioning
confidence: 99%
“…Although criteria for characterizing a piscine epithelial cell line have not been developed, as they have for mammalian epithelial cell lines [ 13 ], several papers describe cultures of gill epithelial cells from fish, including Atlantic salmon [ 12 , 20 – 25 ]. Because neither the ASG-10 nor ASG-13 cell line is cloned, some variation in morphology is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, very few studies have been reported on the epithelial proliferation that may have a profound impact on the health of the fish, regardless of the exact, inciting cause. Establishment of gill cell lines from Atlantic salmon can contribute as a cultivation system for the many pathogenic epitheliotropic gill microorganisms and as a model system to investigate specific cell responses in the gills [ 12 ]. Here, we report the development and characterization of two novel cell lines from Atlantic salmon gill and their potential to propagate different fish viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for a cell line to become established or continuous, it must undergo transformation or immortalization. This can be induced through chemical mutagens, infection with a transforming virus or through transfection (Takarada et al, 1989;Bodnar et al, 1998;Guo et al, 2003;Butler and Nowak, 2004). Immortalization of cells or development of continuous cell line from normal cells requires telomere maintenance apart from optimal culture conditions as pointed out by several researchers (Mathon et al, 2001;Herbert et al, 2002;Wright and Shay, 2002).…”
Section: Limitationsmentioning
confidence: 99%